2020
DOI: 10.1098/rsos.191656
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetic performance of aligned wires assembled from nanoparticles: from nanoscale to macroscale

Abstract: Magnetic wires in highly dense arrays, possessing unique magnetic properties, are eagerly anticipated for inexpensive and scalable fabrication technologies. This study reports a facile method to fabricate arrays of magnetic wires directly assembled from well-dispersed α ″ -Fe 16 N 2 /Al 2 O 3 and Fe 3 O 4 nanoparticles with average diameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…In such a case, the nature of the dipolar interaction changes from ferromagnetic to antiferromagnetic as the orientation of the anisotropy axis varied from perfectly collinear to perpendicularly aligned[45]. Our results with α = 0 • and 90 • are in perfect agreement with the work of Li et al and Yoshida et al[34,49]. We could not compare for other α as they have shown results only with two extremum α values.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…In such a case, the nature of the dipolar interaction changes from ferromagnetic to antiferromagnetic as the orientation of the anisotropy axis varied from perfectly collinear to perpendicularly aligned[45]. Our results with α = 0 • and 90 • are in perfect agreement with the work of Li et al and Yoshida et al[34,49]. We could not compare for other α as they have shown results only with two extremum α values.…”
supporting
confidence: 87%
“…Therefore, these ordered nanoparticles ensembles provide a rich theoretical framework to study the role of dipolar interaction and magnetic anisotropy on magnetic response. Much research efforts ranging from experimental to theoretical modelling have been devoted to unearthing the magnetic properties in such versatile systems [33][34][35][36][37][38][39]. Deng et al presented a detailed and very informative overview regarding forming an anisotropic assembly of MNPs [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials are very interesting for their application as soft materials [2,3]. Such constructions using densely packed particles has also been explored with magnetic nanoparticles [4][5][6]. Another interesting example was reported by Merk, et al [7], where they found that using wood as a template, an anisotropic composite material is obtained, related to the hierarchical structure of wood.…”
Section: Introductionmentioning
confidence: 99%
“…The coercivity is found to significantly modified by the direction of anisotropy axes. Using experiments, Li et al studied the hysteresis response in dense arrays of magnetic nanowires [44]. The coercive field and remanent magnetization are more significant with perfectly aligned anisotropy as compared to perpendicular orientation.…”
Section: Introductionmentioning
confidence: 99%